Investigation of Multiparameter Laser Stripping of AlTiN and DLC C Coatings - Primus, Tomáš; Hlavinka, Josef; Zeman, Pavel; Brajer, Jan; Šorm, Martin; Čermák, Adam; Kožmín, Pavel; Holešovský, František (Materials (Basel, Switzerland), 2021)
The lifetime and properties of cutting tools and forming moulds can be prolonged and enhanced by the deposition of hard, thin coatings. After a certain period of usage, the coating will deteriorate. Any remaining coating must be removed prior to successful recoating. Laser stripping is a fast and environmentally friendly coating removal method. In this paper, we present laser removal of two types of coatings deposited on a 1.2379 tool steel substrate, namely, an AlTiN coating with high hardness and a DLC C coating with a small coefficient of friction (COF). A powerful nanosecond laser was employed to remove the coating from the substrate with high efficiency, along with suitable residual surface roughness. Measurements were taken of surface roughness, removed depth, and working time on a stripped area of 1 cm2. The samples were evaluated under a microscope, with a 3D profilometer, and by EDS chemical analysis. Successful removal of the coating was confirmed by optical analysis, but detailed chemical characterisation showed that about 30% of the coating element may remain on the surface. Moreover, a working time of less than 7.5 s per cm2 was obtained in this study. In addition, it was shown that the application of a second low energy, high frequency laser beam pass leads to remelting of the peaks of the material and reduced surface roughness.
Keywords: DLC C; laser stripping; coating; nanosecond laser; AlTiN